The effect of speaking a minority language at home on foreign language learning. (April 2015) - Maluch, Jessica Tsimprea; Kempert, Sebastian; Neumann, Marko; Stanat, Petra
Abstract: The study investigates the effect of immigrant bilingualism on learning English as a foreign language, controlling for confounding background variables and examining the effect of proficiency in the instructional language at school. Using a sample of 2835 German 6th-graders (Arabic-German: n  = 105, Chinese-German: n  = 110, Polish-German: n  = 57, Turkish-German: n  = 383, heterogeneous bilingual: n  = 284, and monolingual German group: n  = 1896), we examined if speaking another language at home in addition to the instructional language at school presents an advantageous condition for learning English as a foreign language. Controlling for cognitive abilities, age, gender, socio-economic status, parental education, and indicators of cultural capital, the analysis revealed a general positive trend between bilingualism and English foreign language achievement. This positive trend differs significantly between bilingual groups with different home languages. The strongest predictor for foreign language learning revealed to be proficiency in the instructional language. Highlights: There is a positive trend between bilingualism and foreign language outcomes. Instructional language skills are important for foreign language learning. Differences exist between bilingual groups in their foreign language achievement. Background factors explain a noticeable portion of foreign language outcomes.